AKUNTANSI KEPERILAKUAN BERBASIS NILAI-NILAI EKONOMI UNTUK MENINGKATKAN KINERJA RUMAH SAKIT - Anna Marina (UMSurabaya Publishing, 2011)
The purpose of this paper is to determine the role of behavioral accounting based on economic values in improving the performance of hospitals. As a business entity, the hospital is required to continue to expand its commercial customers as well as social needs. It required the support of accounting systems that can be accommodate the changing needs of patients, technology, and human behavior that moves dynamically.Many behavioral theories are available to be used to adjust the design of accounting systems specific hospital. Content Theories such as Maslow's Hierarchy of Needs, Herzberg's Two Factor Theory, Alderfer's ERG Theory as well. Process theory being that can be used is the theory of motivation proposed by Vroom and Porter and Lawler, while the Contemporary Theories of Equity Theory and Attribution Theory.Expected with the use of behavioral theory that according to hospital characteristics can be generated accounting system that can drive sustainable performance by continuous improvement.Key-words: behavioral accounting, accounting systems, hospitals, performance.